Título Padrão: uma análise entre 2010-2020 - Santos, Davilene Souza; Souza, Adriana Serafim de; Rosa, Flávia Goulart Mota Garcia (Informação em Pauta, 2020)
This paper aims to conduct a review in the Brazilian scientific literature on the theme interdisciplinarity and learning processes in a peer-reviewed journal article, indexed in the Journal Portal of the Coordination for the Improvement of Higher Education Personnel (Capes), between 2010 and 2020. The research is of an applied nature, with a qualitative and quantitative approach, adopting content analysis as the techniques. 312 articles were retrieved through the descriptors used, interdisciplinarity and the learning process, after content analysis, this number was reduced to 22 articles, to which further verifications were possible. The categories used for the analyses were: title; summary; Year of publication; authorship; keywords; level; teaching; Journals and Methodological Approach. The survey allowed us to identify that there are some gaps to be researched regarding the studies of this theme at both levels of education, the approaches most used by researchers in their data collection, as well as scientific journals that publish articles on this topic, supporting future investigations.